Zoo studies living collections, their animals and visitors - Rees, Paul A. (Cambridge University Press, 2023)
Zoos and aquariums are culturally and historically important places where families enjoy their leisure time and scientists study exotic animals. Many contain buildings of great architectural merit. Some people consider zoos little more than animal prisons, while others believe they play an important role in conservation and education. Zoos have been the subject of a vast number of academic studies, whose results are scattered throughout the literature. This interdisciplinary volume brings together research on animal behaviour, visitor studies, zoo history, human-animal relationships, veterinary medicine, welfare, education, enclosure design, reproduction, legislation, and zoo management conducted at around 200 institutions located throughout the world. The book is neither 'pro-' nor 'anti-' zoo and attempts to strike a balance between praising zoos for the good work they have done in the conservation of some species, while recognising that they face many challenges in making themselves relevant in the modern world
Title from publisher's bibliographic system (viewed on 17 May 2023)
Keywords: Zoos; Zoos / Educational aspects; Zoos / Management; Zoo animals; Zoo visitors